Motion of charged particles through a barrier created by non-uniform magnetic field with and without radial electric field - Belikov, A.G.; Shariy, S.V.; Yuferov, V.B. (Вопросы атомной науки и техники, 2015)
By numerical calculation a motion of one charged Ar, Kr, Xe ions through the magnetic field barrier was studied (Hmax ~ 1 kG). It was shown that propagation and reflection of the ions is determined by the initial transverse energy of the ions and their masses. Ranges of change of transverse velocities for the particles with different masses that pass through the barrier were evaluated. The influence of direction of a radial electric field that was applied in the region occupied by the linearly decreasing magnetic field, on the particle motion was investigated. It was shown that radial deviation of particles from the axis of symmetry was essentially increased or decreased in comparison to zeroth electric field case depending on the electric fi eld direction. After the particle leaves the crossed-field region the magnitude of its axial velocity can be 1.5...2 times more compared to the starting velocity when the electric field was directed along the radius. Obtained results can be used to minimize the losses of the ions from a particle source by a proper disposition it in the magnetic field and to determine parameters which notably in uence beam formation.